Rethinking Bureaucracy in the Digital Era: A Qualitative Review of Public Sector Transformation in Indonesia - Prasodjo, Tunggul (Manunggal Halim Jaya, 2025)
The digital transformation of public administration has become a crucial aspect of governance, particularly in developing countries like Indonesia, where efforts to modernize the public sector are underway. This study examines digital technologies' impact on Indonesia's bureaucratic structures and governance processes, focusing on the opportunities and challenges associated with integrating digital tools into public administration. The research adopts a qualitative approach, primarily relying on a comprehensive literature review of scholarly articles, government reports, and relevant case studies. This methodology enables a nuanced understanding of how digital governance is implemented and its implications for bureaucratic reform in Indonesia. The findings reveal significant progress in service delivery, transparency, and citizen engagement, with e-government platforms facilitating easier access to public services and promoting greater accountability. However, several challenges persist, such as resistance to change among public sector employees, a digital literacy gap, infrastructure disparities between urban and rural areas, and concerns about data security. The research concludes that while Indonesia has made substantial strides in adopting digital governance, overcoming these barriers requires strategic investments in digital infrastructure, fostering innovation within bureaucratic structures, and ensuring equitable access to digital services. The study also highlights the importance of a flexible and inclusive approach to digital governance to address Indonesia's unique socio-political and cultural challenges.